Antenna with metamaterial design - Halim, Suria (2007)
Metamaterial exhibiting negative permittivity and negative permeability in certain frequency range or known as left-handed material (LHM), provides another alternative to the existing right-hand rule. With this theory, it offers a new dimension to the antenna applications as well as optic. The negative refractive index and the convergence of the electromagnetic waves when passing through the metamaterial is good for optical applications. However, this project looks into the effect of metamaterial structure to the conventional antenna and concentrate on proving the existence of the negative index material within certain frequency regions. Also, the relationship between different varies dimensions used affect the frequency response is being emphasized in order to understand further the metamaterial structure and its properties. Knowing that, the structure is optimized to get the left-handed properties in X-band frequency which is around 8GHz-12GHz. Although, the metamaterial structure giving a limited negative range within the X-band, it does agree to the metamaterial theory with the co-existence of both negative permittivity and negative permeability. The theoretical calculation give a reference value to work with, while the simulation via HFSS simulation tools is used to optimized and confirmed to the theoretical result. Then the simulation also being performed on the antenna with metamaterial structure and the effect is observed and analyzed where we can see a frequency shift occurred.